"I Love Learning; I Hate School" : An Anthropology of College - Blum, Susan D. (Ithaca, NY : Cornell University Press, 2016)
Frustrated by her students' performance, her relationships with them, and her own daughter's problems in school, Susan D. Blum, a professor of anthropology, set out to understand why her students found their educational experience at a top-tier institution so profoundly difficult and unsatisfying. Through her research and in conversations with her students, she discovered a troubling mismatch between the goals of the university and the needs of students.In "I Love Learning; I Hate School," Blum tells two intertwined but inseparable stories: the results of her research into how students learn contrasted with the way conventional education works, and the personal narrative of how she herself was transformed by this understanding. Blum concludes that the dominant forms of higher education do not match the myriad forms of learning that help students-people in general-master meaningful and worthwhile skills and knowledge. Students are capable of learning huge amounts, but the ways higher education is structured often leads them to fail to learn. More than that, it leads to ill effects. In this critique of higher education, infused with anthropological insights, Blum explains why so much is going wrong and offers suggestions for how to bring classroom learning more in line with appropriate forms of engagement. She challenges our system of education and argues for a "reintegration of learning with life."
Frontmatter -- Contents -- Introduction -- Part I. Trouble in Paradise -- Part II. Schooling and Its Oddities -- Part III. How and Why Humans Learn -- Part IV. A Revolution in Learning -- Appendix -- Acknowledgments -- Notes -- Works Cited -- Index -- About the Author
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: College students -- United States -- Attitudes; Motivation in education -- United States; Teacher-student relationships -- United States; Anthropology; EDUCATION / Higher